TINDAK TUTUR DIREKTIF INTERAKSI JUAL BELI MASYARAKAT PANDHALUNGAN - Dela Fitriana; Sankina Windaru Imani; Hilma Azmi Azizah; Saleem Mohd Nasim (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2025)
This research is a descriptive qualitative study using thematic analysis. The focus of this research is to analyze directive speech acts in the buying and selling interactions of the Pandhalungan community. This study employs a descriptive qualitative approach that includes thematic analysis of concepts in pragmatics, specifically focusing on Searle's theory of directive speech acts. The purpose of this study is to determine the directive speech acts that occur during buying and selling by the Pandhalungan community. This study uses a descriptive qualitative research type with thematic analysis. The research data source is the directive speech of the Pandhalungan community in the buying and selling process. Data collection techniques use documentation and free listening techniques. The main instrument in the study is the researcher, who needs supporting instruments such as a data collection guide and a data analysis guide. The data analysis technique used is the theory of Miles and Huberman. The results of this study contain 5 data that can be classified into directive speech acts, namely, 1 requesting sentence, 1 prohibiting sentence, 1 giving permission sentence, and 2 suggesting sentences. This study shows how language is used as a tool for social and cultural negotiation in the economic life of society. Based on this analysis, it can be used as a tool to help understand the complexity and depth of the analysis carried out on buying and selling interactions in the Pandalungan community